Pelatihan Adobe Indesign Pada Guru Smkn 58 Untuk Peningkatan Kompetensi Guru Produktif - Pusparani, Yori; Jatisidi, Artyasto; Satrio Darmawan, Zakaria (Universitas Budi Luhur, 2022)
Software is data that is programmed, stored, and digitally formatted with a specific function. This device itself does not have a physical form, you can operate it via a computer. For its own manufacture, this device requires a programming language written by a programmer/person who is an expert in the field. The reason is, with software that is a command program to run the needs on a computer. Adobe Indesign is a software to layout a magazine or book. In the process of applying Adobe Indesign, all materials are prepared neatly and are in one folder in order to facilitate the place in the process of laying out books or magazines as one of the final goals to be done. Even though it is neat, the important point is how to style a design work in the form of a book or magazine which will later be published to the public. To achieve this, it is necessary to pay attention to various design elements and principles in the layout. Adobe Indesign is often used by designers or smaller is a magazine designer in helping the process of arranging the layout and making it easier to create page by page. This software allows designers to lay out more pages in one book and certainly not too big if used as a raw file. With some of the above foundations, we plan to carry out community service activities with the concept of